Analysis of Mulan’s Image - Chen Chongjie; Selvi Selvi; Vika Bregas Mariza (Lingua Cultura, 2010)
Mulan is an ancient Chinese heroine. The story shows that she is the same as other women, having personal life, but also has a heart that loves her country and her parents. She always thinks about her family, society, dan country. This article was based on library research, using Mulan poem dan a folklore entitled Mulan Pergi Berperang as media to analyze Mulan’s image. It can be said that eventhough at that time there was no gender perspective concept, Mulan had been able  to replace her father to go to war. She gave a lot of contributions for her country, society, and family. Analysis represents that Mulan has three images, as a heroine, as a daughter for her family, and self-image or leader for the women. Having good character and spirit to love country, people, and family make her equal to men. And, it makes her respected by people in each generation.